Analisis Pengembangan dan Evaluasi Virtual World Bertema Lingkungan Pegunungan Menggunakan Metode Research and Development (R&D) - Robby Firmansyah; Andri Firmansyah (Bulletin of Computer Science Research, 2026)
The development of metaverse technology and virtual worlds has created opportunities for utilizing virtual environments as media for digital exploration, simulation, and interactive learning. However, most previous studies have primarily focused on pedagogical aspects and learning simulations, while research discussing the technical development of terrain modeling, lighting, and mountainous environmental atmospheres on the Roblox Studio platform remains limited. This study aims to develop and evaluate a mountainous environment-themed virtual world using Roblox Studio and to analyze user acceptance of the resulting virtual environment. The research employed the Research and Development (R&D) method, consisting of needs analysis, design, implementation, testing, and evaluation stages. The development process utilized Terrain Editor, Future Lighting, skybox, fog, and Lua scripting features to create an interactive virtual environment. Evaluation was conducted using a Likert-scale questionnaire distributed to 67 respondents. The results showed a feasibility score of 79.88%, which falls into the good category. The highest-rated indicator was the suitability of the virtual world to the mountainous environment concept (4.15), while the lowest-rated indicator was the structured layout of the environment (3.83). These findings indicate that the developed virtual world was able to provide a positive exploration experience for users. The contribution of this research lies in establishing a systematic development framework for a mountainous environment-themed virtual world through the implementation of terrain modeling, lighting and atmospheric configuration, and user experience evaluation using the Research and Development (R&D) approach. In addition, this study provides a practical reference for the development of metaverse-based virtual environments that can be utilized for simulation, digital exploration, and interactive learning applications.